2019
DOI: 10.3390/cells8040288
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Receptor Tyrosine Kinase Activity through Alternative Splicing of Ligands and Receptors in the VEGF-A/VEGFR Axis

Abstract: Vascular endothelial growth factor A (VEGF-A) signaling is essential for physiological and pathological angiogenesis. Alternative splicing of the VEGF-A pre-mRNA gives rise to a pro-angiogenic family of isoforms with a differing number of amino acids (VEGF-Axxxa), as well as a family of isoforms with anti-angiogenic properties (VEGF-Axxxb). The biological functions of VEGF-A proteins are mediated by a family of cognate protein tyrosine kinase receptors, known as the VEGF receptors (VEGFRs). VEGF-A binds to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 133 publications
(166 reference statements)
0
28
0
1
Order By: Relevance
“…Neuropilin 2 (NRP2), a cell surface transmembrane protein, was originally characterized as a receptor for type 3 semaphorins (such as SEMA3) and as a co-receptor of VEGFR2 [ 6 ]. NRP2 is primarily expressed in the nervous and vascular systems and is important for the development of embryos by enhancing VEGF-VEGFR binding [ 6 ]. Recent studies have reported that the neuropilin family is involved in tumor metastasis and is correlated with poor prognosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropilin 2 (NRP2), a cell surface transmembrane protein, was originally characterized as a receptor for type 3 semaphorins (such as SEMA3) and as a co-receptor of VEGFR2 [ 6 ]. NRP2 is primarily expressed in the nervous and vascular systems and is important for the development of embryos by enhancing VEGF-VEGFR binding [ 6 ]. Recent studies have reported that the neuropilin family is involved in tumor metastasis and is correlated with poor prognosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that VEGF facilitates aberrant tumour angiogenesis in vitro (Stevens & Oltean, 2019). We examined whether VEGF promotes EPC angiogenesis in vivo.…”
Section: Vegf Facilitates Epc-induced Angiogenesis In Vivomentioning
confidence: 99%
“…VEGF/VEGFR VEGF/VEGFR axis plays a key role in both physiological and pathological vascularization in diseases such as tumor angiogenesis. [68][69][70][71] There are five distinct VEGF family members in a mammal: VEGF-A (also referred to as VEGF), VEGF-B, VEGF-C, VEGF-D, and placenta growth factor (PLGF). VEGFR family consists of RTK member, including VEGFR1, VEGFR2, and VEGFR3, as well as the non-tyrosine kinase co-receptors neuropilin-1 (NP-1) and NP-2.…”
Section: Her2mentioning
confidence: 99%